A comparative study of serum total thyroxine estimation on unextracted serum by radioimmunoassay and by competitive protein binding. Issue 8 (August 1975) - Marsden, P; Facer, P; Acosta, M; Howorth, P J
Abstract : A rapid and precise radioimmunoassay (RIA) for serum total thyroxine (T4) on as little as 1-10 mul of unextracted serum is described. Results in hypothyroidism (overt and borderline), in euthyroid subjects in pregnant and oestrogen-medicated subjects, and in hyperthyroidism (overt and borderline) are compared with the results on the same sera by an established competitive protein binding technique (Ames' Tetralute) on unextracted serum from a different laboratory. The correlation between the two methods was excellent (r= 0.94) and no significant difference between overall appeared to measure total T4 Reliaby in sera containing only 1-3 or 2-6 nmol/1. Both methods predicted the clinical outcome in borderline hypothyroidism and borderline hyperthyroidism equally well and both gave normal results in T3-toxicosis. It is concluded that both techniques reliably measure total T4- RIA appears to have advantages of sensitivity and precision (especially in the hypothroid range), of simplicity, and of low cost.